Еволюція аналізу теорій причин злочинності в першій половині XX століття - Нежурбіда, С.; Нежурбида, С.; Nezhurbida, S. (Одеса : Юрид. л-ра, 2012)
In the article the author explores the evolution of crime causation theories analysis during the XX half-century. One of the author's conclusion is the conclusion about the domination of «promotion»-analysis of crime causation theories in mentioned period.
Нежурбіда С. Еволюція аналізу теорій причин злочинності в першій половині XX століття / С. Нежурбіда // Актуальні проблеми держави і права : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 478-484.
Keywords: еволюція; аналіз; теорія; причина; злочин; злочинність; эволюция; анализ; теория; причина; преступление; преступность; evolution; analysis; theory; cause; crime; criminality